“Factores de riesgos laborales del puesto de trabajo del personal administrativo en la central termoeléctrica Quevedo II corporación eléctrica del Ecuador Empresa Pública (CELEC EP)”. - Napa Peralta, Luis Alfredo (2016)
This research was designed to determine factors occupational risk jobs administrative staff in the Central Termoelectrica Quevedo II Corporation Public Company Electrica del Ecuador (Celec Ep); for demonstration were available Colombian technical guide GTC 45 and through which were identified and quantified 16 occupational risk factors among them physical, ergonomic and psychosocial risks were found, thus leaving the level of probability and risk level among media and high, analyzed in 26 jobs. It was determined by using international methodologies and the respective measurements with certified equipment and this in turn showed that levels of luxes two jobs are not acceptable, on the other hand the other positions are less acceptable; while for the sound pressure level and temperature are at acceptable levels. Also evaluated through the ROSA method ergonomic risk in the chair and mouse factor is high with a small percentage, finally through psychosocial test it was obtained that 5 % of the 24 workers have very high risk factor time work, 38 % in the workload, 17 % in psychosocial demand, 29 % in participation / monitoring, 4 % in the performance of role and finally 8 % in relationships and social support. Keywords: Occupational hazard; (Physical, ergonomic and psychosocial) and job